2001
DOI: 10.1046/j.1440-1789.2001.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of non‐functioning pituitary adenoma with Cushing's syndrome upon recurrence

Abstract: A 49-year-old woman presented with left visual disturbance. No signs of Cushing's disease were evident. Basal levels of serum cortisol and plasma adrenocorticotropic hormone (ACTH) were 16.8 microg/dL and 66.0 pg/mL, respectively. MRI demonstrated an irregularly shaped large pituitary tumor, and the patient then underwent transsphenoidal surgery. By light microscopy the tumor represented a chromophobic adenoma with a few of the adenoma cells showing immunoreactivity for ACTH. On the basis of clinical and light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Subtype II adenomas are chromophobic, lack cytokeratin filaments, have scattered PAS staining, sparse ACTH staining, and lower Tpit expression [1] [12,16,20]. In addition to corticotroph features, SCAs incorporate gonadotroph elements as evidenced by the presence of honeycomb Golgi [48,64] and increased mitochondrial density [64]. In our series, two SCAs tested were categorized as SCA subtype II while the remainder incorporated elements of both corticotroph and gonadotroph adenomas.…”
Section: Pathologymentioning
confidence: 87%
See 1 more Smart Citation
“…Subtype II adenomas are chromophobic, lack cytokeratin filaments, have scattered PAS staining, sparse ACTH staining, and lower Tpit expression [1] [12,16,20]. In addition to corticotroph features, SCAs incorporate gonadotroph elements as evidenced by the presence of honeycomb Golgi [48,64] and increased mitochondrial density [64]. In our series, two SCAs tested were categorized as SCA subtype II while the remainder incorporated elements of both corticotroph and gonadotroph adenomas.…”
Section: Pathologymentioning
confidence: 87%
“…A number of individual cases of SCAs were reported to transform to symptomatic functioning Cushing Disease, notably after receiving radiotherapy [3,4,6,14,32,60,64]. However, in large series of SCAs, 2 groups each reported only 1 case transforming to biochemical Cushing disease but without clinical stigmata [19,61].…”
Section: Clinical Coursementioning
confidence: 99%
“…Indeed, just a few similar cases have been reported, mostly in isolated case reports or series not focused on this topic, and no overall view of this phenomenon and its clinical implications has been provided. 1,3,6,13,[15][16][17]20 Vaughan et al 17 and Cooper et al 6 were among the first to report the development of Cushing disease from a previously silent ACTH adenoma. Subsequently, a few other authors have reported this same phenomenon and have shown the potential of silent ACTH adenomas to shift to a functioning form during the follow-up period, even many years after the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a few other authors have reported this same phenomenon and have shown the potential of silent ACTH adenomas to shift to a functioning form during the follow-up period, even many years after the initial diagnosis. 1,13,15,16,20 It is interesting to note that Brown et al 3 demonstrated the possibility of silent ACTH adenomas evolving into corticotropin-secreting carcinomas long after the initial diagnosis (16 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation